Coaching tools in education as an instrument to develop new competencies of higher education managers - Aiache, Adriana; Centurion , Diosnel (Seven Editora, 2023)
The present study aimed to analyze the coaching process in the context of academic management with managers and staff of the academic administration of the Faculty of Administration and Business (Conveniada FGV). The study was based on the non-experimental model, descriptive type of the case study modality, with a mixed approach - qualitative and quantitative. Data were collected from a population of coordinators, directors and teachers through questionnaires with open and closed questions. The results show that coaching offers highly effective collaboration, in which the sharing and dissemination of skills and competencies that create a powerful learning platform from its tools for leaders, managers, teachers and support staff. As well as proving that by learning coaching skills it provides teachers with the tools to help learners find their own solutions to problems, take risks and become comfortable with challenge and change. Therefore, it is concluded that coaching can be used by both academic management and administration staff, teachers and students to create a powerful learning environment. It states that effective feedback needs to be specific and clearly linked to performance, and that peer teaching needs to be learned as a skill to get the best results. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-029